Effect of different types of feed (squid, sea worms, and trash fish) to gonad maternity and fundamental levels of Galah shrimp (Macrobrachium Rosenbergii) - Ganjar Adhywirawan Sutarjo; David Hermawan; Alvi Zahrotun Nisa (IJOTA (Indonesian Journal of Tropical Aquatic), 2021)
Giant prawns (Macrobrachium rosenbergii) need enough nutrients for the reproductive process. One way to give feed which contains high enough protein. Complete nutritional content, especially protein, can be found in natural food. The type of natural feed used for main feeds including squid, sea worms, trash fish. Complete nutrient content can affect the rate of gonadal development and fecundity. (Squid, sea worms, trash fish) on the level of gonadal maturity and density of broodstock parents (Macrobrachium rosenbergii). This research was conducted by a completely randomized design (CRD) trial design. This study used 4 replications of different types of feeding. The types of feed given are squid, sea worms, trash fish, and pellets at a dose of 5% from biomass/day. The parameters of observation include observation of the level of gonad resistance, fundamentality of broodstock parent, and measurement of water quality (temperature, pH, and dissolved oxygen). The results showed that the administration of different types of feed (sea worms, trash fish) had a very significant effect on the level of maturity and had a significant effect on the probability of prawns (M. rosenbergii). After analysis of variance, the results of F Calculations are greater than F Table 0.05 and F Table 0.01. The smallest significant difference test (LSD) was obtained in P1 (Squid feed) with the Gonad maturity rate ± 5- 6 days as much as 83 % parent and fecundity average results of 28,846 ± 4,925.3 thousand / 45 g.